Understanding and analyzing the mediation efforts of SADC during regional crises: the case of Madagascar - Ramsamy, Katiana Sandra (My University, 2021)
In March 2009, President Marc Ravalomanana of the Island of Madagascar was ousted during a coup d’étatled by the Mayor of Antananarivo, Andry Rajoelina, and his supporters. After the coup, Ravalomanana and his family fled to South Africa where they remained in exile from 2009 to 2014. To restore constitutional order in Madagascar, the Southern African Development Community (SADC), in July 2009, took the lead in a mediation process involving all Malagasy and other key stakeholders. SADC’s mediation efforts, led by former President Chissano, formally ended in 2013 with the holding of democratic elections. The mediation effort, which lasted five years, was conducted in a competitive and “crowded” field. The “crowded” field was characterised by in-fighting amongst the various international bodies for power and influence including “spoiler” tactics used by vested interests to hinder the mediation process and prevent the return of Ravalomanana to Madagascar. This thesis critically examined SADC’s mediation efforts in the aftermath of the 2009 coup d’état and determined whether SADC was effective in achieving its main mandate–that of restoring constitutional order in Madagascar through democratic elections. Mediation, as defined in this thesis, is the process whereby a third party assists warring and conflicting parties, with their consent, to prevent, manage or resolve a conflict by developing mutually acceptable agreements. To set the scene, the various theoretical concepts and studies on mediation and conflict resolution were analyzed to improve the general understanding on how these can contribute to effective policy actions geared towards the mediation-based resolution in southern Africa and beyond. This analysis was key in understanding the mediation process undertaken by SADC in Madagascar. The various theoretical concepts and studies on mediation were also applied to the case of SADC’s mediation in Madagascar. The comprehensive analysis of the outcomes of various conflict resolution agreements reached between 2009 and 2013 to resolve the crisis and the attitudes of the conflicting parties also provided useful knowledge and clear insights on mediation. It revealed the unwavering commitment of SADC to bring constitutional order to Madagascar and the resilience of the SADC mediators under the leadership and expertise of former President Chissano. Chissano used different mediation techniques, such as adaptive mediation and proximity talks, to engage the conflicting parties, including those who had vested interests in Madagascar. The thesis provides (i) additional insight on the existing body of knowledge on international mediation that will be useful for regional mediators, for policymakers (especially in Africa) and for future mediation processes, and (ii) additional and intellectual insight on the existing, but limited, body of knowledge about SADC mediation’s efforts in Madagascar. Currently, the available research on SADC’s mediation in Madagascar predominantly focuses on SADC’s challenges and flaws, as opposed to its accomplishments. The research concluded that mediation remains the most effective tool for conflict resolution. After five years of mediation efforts, with all the challenges and setbacks, SADC managed to fulfil its mandate of returning Madagascar to constitutional order. The SADC amended Roadmap, which was accepted by all the conflicting, paved the way for democratic elections to be held on 25 October 2013
A thesis submitted in fulfilment of the requirements of the degree of Doctor of Philosophy (PhD) in the Faculty of Humanities, University of the Witwatersrand, 2021